Understanding Recent Inflationary Dynamics in Ireland - Dermot P. Coates; Rory Mulholland; Keith Fitzgerald; Karen Hogan; Hugh Creaton (National Competitiveness and Productivity Council (NCPC), 2023)
After peaking in October 2020 at 9.2%, Ireland's CPI currently stands at an annual change of 5.8% in July 2023. Looking at producer prices, by June 2023, Ireland's Producer Price Index (PPI) had fallen 3.1% year-on-year in contrast to the PPI of the US, UK, and EA over the same period. The main drivers of overall inflation are observed in the categories of energy, housing, and food costs. Although forecasts predict that levels of inflation will ease over the coming years, external factors such as climate change and the ongoing war in Ukraine may mitigate the rate at which inflation moderates. Tightening monetary policy aims at reducing inflation both by dampening demand via the increased cost of borrowing and setting long-term expectations. These rate rises, combined with an increasing number of customers re-setting their mortgages at higher interest rates, will see many households facing increased mortgage costs.
Keywords: 330